Synthesis of Cyclopentapyridine and Thienopyridine Derivatives as Potential Calcium Channel Modulators - Gündüz, M. G.; Şafak, C.; Kaygısız, B.; Koşar, B. Ç.; Şimşek, R.; Erol, K.; Linden, A. (Arzneimittelforschung, 2012)
In this study, novel condensed 1,4-dihydropyridines bearing cyclopentanone (1–21) or tetrahydrothiophene-1,1-dioxide ring (22–42) with various ester substituents were synthesized via a modified Hantzsch reaction and their calcium channel modulator activities were investigated on isolated rat ileum and rat thoracic aorta. The introduction of a cyclopentanone ring fused to the 1,4-dihydropyridine nucleus and methyl, ethyl and allyl moieties to the ester group led to more active calcium modulators.
Keywords: 1,4-Dihydropyridine; thienopyridine; cyclopentapyridine; calcium channel modulator